Prevalensi Penyakit Malaria dan Hubungannya dengan Tingkat Pengetahuan pada Masyarakat di Baturinggit Selatan - Musparlin Halid (Universitas Islam Negeri Mataram, 2018)
Malaria is a common public health problem in the rainy season that can result in transmission to others and even death. Most neighborhoods in the Asian Region underscore immediate effective preventive measures such as control strategies especially in young children and pregnant women. Efforts can be made in vector control of malaria disease by studying the level of knowledge and environmental management around their homes. The objective of the study was to identify the prevalence of malaria and its relation with the level of knowledge in the community. Research design was cross sectional design in South Baturinggit in July - December 2017. The sample was 148 families. The variables measured were malaria prevalence and knowledge level as the main variable. While supporting variables such as gender and age. Data were analyzed using chi square statistic test (χ2) with significant level p<0,05. The results showed that sex factor did not have significant relationship to malaria incidence with p>0,05. The prevalence of malaria was quite high in the South Baturinggit Environment caused by the environmental management factor around the house and the low level of public knowledge.